Effect of government role and human resource competence on level of success of small and medium enterprises in East Java province with business performance as mediation variable - Al Idrus, Salim; Abdussakir, Abdussakir; Al Idrus, Shofiyah; Supriyanto, Achmad Sani; Ahmar, Ansari Saleh; Kamaluddin, Kamaluddin (Jurnal Ekonomi Modernisasi, 2023)
The objective of this research is to reveal the effect of government role and human resource competence on level of success of SMEs in East Java Province with business performance as mediation variable. Using quantitative research, causal relationship across variables is ensured through SEM-PLS method. Sampling technique is purposive random sampling with 130 SMEs used as sample. Data collection technique is using questionnaire. The results of research show that government role and human resource competence affect level of success of SMEs in East Java Province; and business performance is the mediation variable to the effect of government role and human resource competence on level of success of SMEs in East Java Province.